Health programmes and services addressing the prevention and management of infectious diseases in persons who inject drugs in Canada: a systematic integrative review protocol. Issue 8 (13th August 2020) - Alvarez, Elizabeth; Joshi, Siddharth; Lokker, Cynthia; Wang, Annie; Pavalagantharajah, Sureka; Qiu, Yun; Sidhu, Hargun; Mbuagbaw, Lawrence; Qutob, Majdi; Henedi, Alia; Levine, Mitchell; Lennox, Robin; et al.
Abstract : Introduction: Injection drug use (IDU) and intravenous drug use (IVDU) are of concern to the people using drugs, their families and health systems. One of the complications of IDU/IVDU is the risk of infection. Clinical experience has shown that persons who inject drugs (PWID) are hospitalised and re-hospitalised frequently. In Canada there are sparse data about the reasons for which PWID are admitted to hospital and their health trajectories, especially for infectious diseases. There are special concerns regarding PWID with infections who leave the hospital against medical advice and those who leave with a peripherally inserted central catheter line in place for administration of long-term antibiotics or other therapies. Improving our understanding of current programmes and services addressing the prevention and management of infectious diseases and their complications in PWID could lead to focused interventions to enhance care in this population. Methods and analysis: An integrative systematic review allows for inclusion of a variety of methodologies to understand a health issue from different viewpoints. PubMed, CINAHL, Web of Science Databases and websites of the Public Health Agency of Canada, Canadian Institute for Substance Use Research, and Canadian Centre on Substance Use and Addiction will be searched using terms for infectious diseases, drug use and geography (Canada) and limited to the last 10 years (2009–2019). The Quality Appraisal Tool in Studies with Diverse Designs will be used to appraise the quality of identified studies and documents. Quantitative, qualitative or mixed methods data synthesis will be used as needed. Ethics and dissemination: This study is a secondary analysis of publicly available documents; therefore, no ethics approval is required. This information will inform a research agenda to further investigate interventions that aim to address these issues. PROSPERO registration number: CRD42020142947.